Characterization of Clinical Isolates of Enterococci with Special Reference to Glycopeptide Susceptibility at a Tertiary Care Center of Eastern Nepal - Aasish Karna; Ratna Baral; Basudha Khanal (International Journal of Microbiology)
Background. Enterococci, once considered as a harmless commensal of intestine, have now emerged as medically important pathogens and are associated with both community-acquired and nosocomial infections. They bear the potential to exhibit resistance against all commonly used antibiotics either by inherent or acquired mechanism, posing a therapeutic challenge. Objectives. This study aimed to characterize enterococci up to the species level and study their antibiogram with special regard to vancomycin. Methods. A descriptive cross-sectional study was conducted in the Department of Microbiology, B.P. Koirala Institute of Health Sciences, Dharan, Nepal, from February to May 2017. A total of 91 enterococcal isolates recovered from clinical specimens were investigated in this study. Their identification and speciation were done according to standard microbiological guidelines. Kirby–Bauer disc diffusion technique was used to study antimicrobial susceptibility pattern, whereas minimum inhibitory concentration of vancomycin was determined by the agar dilution method, with reference to Clinical and Laboratory Standards Institute guidelines. Results. Seven different species of enterococci were isolated, E. faecalis and E. faecium accounting about 45% each. The other species encountered were E. avium, E. cecorum, E. dispar, E. durans, and E. raffinosus. Highest proportion of antimicrobial susceptibility was recorded for linezolid (97.8%), followed by teicoplanin (95.6%) and high-level gentamicin (81.3%). Sensitivity to vancomycin was seen in 79.1% isolates. Likewise, 82.1% of urinary strains were susceptible to nitrofurantoin. A total of 4 disparities were observed between the disc diffusion technique and agar dilution method in determining vancomycin resistance. Multidrug resistance was observed in 31.9% isolates. The overall prevalence of vancomycin-resistant enterococci based on the standard minimum inhibitory concentration method was 25.3%. Conclusions. Enterococcus faecalis and E. faecium were the predominant species in causing enterococcal infections. The alarming rise in prevalence of vancomycin and multidrug resistance strains warrants immediate, adequate, and efficient surveillance program to prevent and control its spread.